(untitled) (Journal of Engineering, 2015)
Unsaturated soil can raise many geotechnical problems upon wetting and drying resulting in swelling upon wetting and collapsing (shrinkage) in drying and changing in the soil shear strength. The classical principles of saturated soil are often not suitable in explaining these phenomena. In this study, expansive soil (bentonite and sand) were tested in different water contents and dry unit weight chosen from the compaction curve to examine the effect of water content change on soil properties (swelling pressure, expansion index, shear strength (soil cohesion) and soil suction by the filter paper method). The physical properties of these soils were studied by conducting series of tests in laboratory. Fitting methods were applied to obtain the whole curve of the SWRC measured by the filter paper method with the aid of the (Soil Vision) program. The study reveals that the initial soil conditions (water content and dry unit weight) affect the soil cohesion, soil suction and soil swelling, where all these parameters marginally decrease with the increase in soil water content especially on the wet side of optimum.